2012
DOI: 10.1155/2012/768101
|View full text |Cite
|
Sign up to set email alerts
|

A Nonpolar Blueberry Fraction Blunts NADPH Oxidase Activation in Neuronal Cells Exposed to Tumor Necrosis Factor-α

Abstract: Inflammation and oxidative stress are key to the progressive neuronal degeneration common to chronic pathologies, traumatic injuries, and aging processes in the CNS. The proinflammatory cytokine tumor necrosis factor-alpha (TNF-α) orchestrates cellular stress by stimulating the production and release of neurotoxic mediators including reactive oxygen species (ROS). NADPH oxidases (NOX), ubiquitously expressed in all cells, have recently emerged as pivotal ROS sources in aging and disease. We demonstrated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Together, the assembly of this complex forms the functional NOX2 enzyme. NOX2 isoforms are ubiquitously expressed, and they are present in the lungs endogenously in the steady state and are overabundant during inflammatory conditions (16,30,60,156). The main NOX2-expressing cell types within the respiratory tract include alveolar macrophages, dendritic cells, and/or other resident or infiltrated inflammatory-immune cells (e.g., neutrophils, eosinophils, and lymphocytes) ( Fig.…”
Section: Fig 2 Schematic Illustrationmentioning
confidence: 99%
“…Together, the assembly of this complex forms the functional NOX2 enzyme. NOX2 isoforms are ubiquitously expressed, and they are present in the lungs endogenously in the steady state and are overabundant during inflammatory conditions (16,30,60,156). The main NOX2-expressing cell types within the respiratory tract include alveolar macrophages, dendritic cells, and/or other resident or infiltrated inflammatory-immune cells (e.g., neutrophils, eosinophils, and lymphocytes) ( Fig.…”
Section: Fig 2 Schematic Illustrationmentioning
confidence: 99%
“…However, other studies imply that processing techniques may have little influence on oxygen radical absorbance capacity [16]. It has been established that 5 g/ml of crude WBB extract significantly decreases the level of induced reactive oxygen species in SH-SY5Y cells [26]. Additionally, crude WBB extract does not compromise SH-SY5Y cell viability up to 75 g/ml [27].…”
Section: Controlmentioning
confidence: 99%
“…Therefore, the novelty of this study was to demonstrate the antioxidant effect of a novel divinyl sulfide compound on an in‐vivo model of oxidative stress. In addition, ((4‐ tert ‐butylcyclohexylidene) methyl) (4‐methoxystyryl) sulfide is a non‐polar compound and other studies have demonstrated that non‐polar agents showed higher cerebral antioxidant effect than polar ones [54,55]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ((4-tert-butylcyclohexylidene) methyl) (4-methoxystyryl) sulfide is a non-polar compound and other studies have demonstrated that non-polar agents showed higher cerebral antioxidant effect than polar ones. [54,55] The exact mechanism to explain the antioxidant action of sulfide is not clear at the moment. However, we can speculate that this compound acts on different antioxidant defence mechanisms, which was clearly demonstrated by the efficiency of this compound in restoring the cerebral oxidative damage induced by SNP.…”
Section: Discussionmentioning
confidence: 99%